Purpuric rash in an adolescent - Melo, Joana; Margalha Miranda, Ana; Pereira Fernandes Garcês, Sónia (BIRTH AND GROWTH MEDICAL JOURNAL, 2025)
A previously healthy 17-year-old girl presented to the emergency department with a 14-day history of fever, sore throat, and a generalized reddish-purple pruritic rash. The rash, initially erythematous and maculopapular, worsened and became coalescent and purpuric. She had been treated with azithromycin for three days starting on the third day of illness. Physical examination revealed a good general condition, pharyngeal erythema with exudate, and a purpuric rash covering the body, including the face, palms, and soles, without other systemic signs. Serological tests confirmed a diagnosis of acute infectious mononucleosis. The patient was managed conservatively and had fully recovery at re-evaluation, 50 days after symptom onset. Acute infectious mononucleosis typically presents with fever, cervical lymphadenopathy, and tonsillitis/pharyngitis, with spontaneous exanthema occurring in 3-15% of cases. This case highlights the importance of considering acute infectious mononucleosis in adolescents presenting with purpuric exanthema and the potential for antibiotic-associated rash including azithromycin, emphasizing the need for thorough clinical and serological evaluation.